Small- and Medium-Sized Companies Tackling the Digital Transformation of Supply Chain Processes: Insights From a Multiple Case Study in the German Manufacturing Industry - Birkel, Hendrik; Wehrle, Manuel (IEEE Transactions on Engineering Management, 2022)
Current research lacks in-depth insights into the digital transformation management of supply chain (SC) processes in small- and medium-sized enterprises (SMEs) from an intrafirm level perspective. Therefore, the aim of this article is to investigate how SMEs strategically and organizationally manage the digital transformation of SC processes to ascertain the reasons for the low penetration of digitally transformed SC processes. To address the challenges arising from digital transformation, we conduct a multiple case study with 15 highly knowledgeable stakeholders from seven companies within the German manufacturing industry using semistructured interviews. Our findings are varied and indicate that explicitly formulated digital SC strategies are absent in SMEs, but companies use three different approaches to digitally transform their SC processes. Accordingly, the article reveals how these approaches are organizationally implemented and explains the barriers impeding further digital SC process transformation in SMEs, such as insufficient attention by upper management, uncoordinated initiatives due to uncertainty, and inadequate operational capabilities. In addition, the article confirms the link between the creation of transparency and organizational structure. Consequently, this article is one of the first to enhance the knowledge of digital process transformation by examining the existing core transformation principles of SMEs, developing a bottom-up implementation model, holistically analyzing barriers, and necessary prerequisites to the digital transformation of SC processes, providing in-depth managerial implications, and laying the foundation for further research endeavors.
CRIS-Team WoS Importer:2022-10-21